Measurement of the leptonic charge asymmetry in ttW± production using the trilepton final state in proton-proton collisions at √ s = 13 TeV using the ATLAS experiment - Garvey, Cameron (Department of Physics, 2022)
In this dissertation, a measurement of the leptonic charge asymmetry (A ` C ) in top quark pair production in association with a W boson (t ¯tW±) is presented. The A ` C is sensitive to new physics beyond the standard model, such as the axigluon and as a result, a measurement of the A ` C could prove useful in searches for new physics. The data set used in this measurement consists of proton-proton collisions at the Large Hadron Collider (LHC) at √ s = 13 TeV, which was recorded using the ATLAS experiment and corresponds to an integrated luminosity of 139 . An event selection scheme was put in place to optimally select for t ¯tW± events in the trilepton final state while suppressing background events. The A ` C is calculated using the pseudorapidities of the two leptons that decay from a top quark and a top anti-quark. A lepton-top association was implemented using machine learning which was used to correctly identify the leptons which decay from top quarks in 72% of t ¯tW± events. Using the results obtained from the lepton-top association, the A ` C was measured using a method called the fit across regions (FAR) method. This method makes use of machine learning to differentiate between signal (t ¯tW±) and all of the backgrounds to increase the sensitivity to the A ` C . Using the FAR fit, a leptonic charge asymmetry of A ` C = -9 % ± 22 % was extracted from Asimov data which is consistent with Standard Model prediction of the A ` C , as expected. Results of a fit to the ATLAS data remain blinded as this analysis forms the basis of an official ATLAS measurement which is yet to be published. The dominant source of uncertainty results from the limited size of the data set. Further data acquired at the LHC over the next decade should reduce the impact of the dominant uncertainty of the measurement of the A ` C in t ¯tW±.